If you build it, will they eat it? Consumer preferences for plant-based and cultured meat burgers. (1st June 2018) - Slade, Peter
Abstract: In a hypothetical choice experiment consumers were given the option of purchasing burgers that were made from beef, plant-based protein, or cultured meat. Willingness to purchase plant-based and cultured meat burgers is linked to age, sex, views of other food technologies, and attitudes towards the environment and agriculture. Although consumers were told that all burgers tasted the same, there was a marked preference for beef burgers. A mixed-logit model predicts that, if prices were equal, 65% of consumers would purchase the beef burger, 21% would purchase the plant-based burger, 11% would purchase the cultured meat burger, and 4% would make no purchase. Preferences for plant-based and cultured meat burgers are found to be highly, but not perfectly, correlated.